Apparel Consumption and Embodied Experiences of Gay Men and Transgender Women in India: Variety and Ambivalence, Fit Issues, LGBT-Fashion Brands, and Affordability. Issue 9 (29th July 2021) - Chauhan, Vishakha; Reddy-Best, Kelly L.; Sagar, Mahim; Sharma, Arbuda; Lamba, Karan
ABSTRACT: The purpose of this study was to explore Indian LGBT individuals' apparel consumption practices and embodied experiences related to fashion, style, and the body. Specifically, our research questions were these: What are Indian LGBT individuals' experiences like when navigating the fashion system, and how do they experience their own embodiment in what they wear and how they appear? A qualitative, phenomenological approach was used to answer the research questions. Three gay men and seven transgender women responded to a solicitation for participation and completed a semistructured interview. In our data analysis, we established four themes that relate to two larger areas of emphasis: embodiment and the fashion system. Regarding embodiment, participants related many experiences with their bodies, including (a) variety and ambivalence with bodily practices and (b) difficulty with clothing fit. The other themes centered around knowledge and desires related to the fashion system. Within the fashion system, participants expressed (a) fashion brand awareness and a need for LGBT-centered brands and (b) affordability as a barrier to clothing purchase. Overall, the essence of fashioning one's body as a transgender woman or gay man in India is that, while there has been a significant amount of gender oppression in India, these participants were interested in and desired gender-neutral or LGBT-focused brands.